2021
DOI: 10.1101/2021.09.08.459545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genome of the endangeredMacadamia janseniidisplays little diversity but represents an important genetic resource for plant breeding

Abstract: Macadamia, a recently domesticated expanding nut crop in the tropical and subtropical regions of the world, is one of the most economically important genera in the diverse and widely adapted Proteaceae family. All four species of Macadamia are rare in the wild with the most recently discovered, M. jansenii, being endangered. The M. jansenii genome has been used as a model for testing sequencing methods using a wide range of long read sequencing techniques. Here we report a chromosome level genome assembly, ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Heterozygosity between the haplotypes in diploids can complicate the genome assemblies. The low heterozygosity of M. jasnenii and high heterozygosity of M. integrifolia and M. tetraphylla (Sharma et al, 2021b;Xia et al, 2022;Nock et al, 2020b;Niu et al, 2022) was also supported by k-mer analysis, haploid assembly statistics and dotplot comparisons. The dotplot comparison of the two M. jansenii haploid assemblies, showing minimal differences between the two.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations

The genomes of theMacadamiagenus

Sharma,
Masouleh,
Constantin
et al. 2023
Preprint
Self Cite
“…Heterozygosity between the haplotypes in diploids can complicate the genome assemblies. The low heterozygosity of M. jasnenii and high heterozygosity of M. integrifolia and M. tetraphylla (Sharma et al, 2021b;Xia et al, 2022;Nock et al, 2020b;Niu et al, 2022) was also supported by k-mer analysis, haploid assembly statistics and dotplot comparisons. The dotplot comparison of the two M. jansenii haploid assemblies, showing minimal differences between the two.…”
Section: Discussionmentioning
confidence: 63%
“…The comparison of genome assemblies of the already available genomes of M. jansenii, M. integrifolia, and M. tetraphylla with those generated in this study revealed notable improvements in the assembly statistics. For M. jansenii, the newly assembled genome demonstrated an increase in length (from 758Mb to 773Mb), improvement in N50 value from 52Mb to 55Mb and slight improvement in BUSCO as compared to the already available M. jansenii Hi-C assembly's 758 Mb (Sharma et al, 2021b). This study has greatly improved the M. integrifolia (cultivar 741) genome with a longer assembly length of 775 Mb and a significantly higher BUSCO of 97% and N50 value of 53 Mb as compared to previous assemblies by Nock et al, in 2016 (N50: 4.7 kb) & 2020 (N50: 413 kb) (Nock et al, 2016;Nock et al, 2020b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation

The genomes of theMacadamiagenus

Sharma,
Masouleh,
Constantin
et al. 2023
Preprint
Self Cite